2005
DOI: 10.1104/pp.105.062349
|View full text |Cite
|
Sign up to set email alerts
|

Light-Dark Changes in Cytosolic Nitrate Pools Depend on Nitrate Reductase Activity in Arabidopsis Leaf Cells

Abstract: ; and Crop Performance and Improvement Division, Rothamsted Research, Harpenden, Hertfordshire AL5 2JQ, United Kingdom (S.J.C., A.J.M.)Several different cellular processes determine the size of the metabolically available nitrate pool in the cytoplasm. These processes include not only ion fluxes across the plasma membrane and tonoplast but also assimilation by the activity of nitrate reductase (NR). In roots, the maintenance of cytosolic nitrate activity during periods of nitrate starvation and resupply (M. va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 52 publications
9
62
0
2
Order By: Relevance
“…Considering AtClCa within the plant cell context, with a gradient of 2 pH units (pHvac 5.5, pHcyt 7.5) and a transmembrane potential of K30 mV between the cytosol and the vacuole (figure 1), the 2NO K 3 =1H C exchange mechanism allows an accumulation of nitrate in the vacuole by a factor of 50, whereas a channel could only drive a threefold accumulation. Interestingly, the measured NO K 3 concentration gradient between vacuole and cytosol in A. thaliana mesophyll cells (Coockson et al 2005) falls within the same range as that potentially built up by the AtClCa NO K 3 /H C exchanger. A transient transformation system of mesophyll protoplasts extracted from mutant plants was set up with a dual objective: (i) to demonstrate that the knockout mutants were functionally complemented by AtClCa cDNA, and (ii) to set up an expression system suitable for electrophysiological experiments to investigate AtClCa structure-function relationships.…”
Section: The Plant Clc Familymentioning
confidence: 55%
“…Considering AtClCa within the plant cell context, with a gradient of 2 pH units (pHvac 5.5, pHcyt 7.5) and a transmembrane potential of K30 mV between the cytosol and the vacuole (figure 1), the 2NO K 3 =1H C exchange mechanism allows an accumulation of nitrate in the vacuole by a factor of 50, whereas a channel could only drive a threefold accumulation. Interestingly, the measured NO K 3 concentration gradient between vacuole and cytosol in A. thaliana mesophyll cells (Coockson et al 2005) falls within the same range as that potentially built up by the AtClCa NO K 3 /H C exchanger. A transient transformation system of mesophyll protoplasts extracted from mutant plants was set up with a dual objective: (i) to demonstrate that the knockout mutants were functionally complemented by AtClCa cDNA, and (ii) to set up an expression system suitable for electrophysiological experiments to investigate AtClCa structure-function relationships.…”
Section: The Plant Clc Familymentioning
confidence: 55%
“…Nitrate storage in the vacuole takes place during the night, when nitrate reductase is inactive. NO 3 Ϫ is then released from the vacuole during the day, when the requirement of nitrate by nitrate reductase is high (34). The cytosolic ATP and AMP pools have been shown to regulate nitrate reductase activity and to vary together with the photosynthetic status of the cell (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the middle of the wall there was a 2.53130.5 cm hole and a tie to hold the tissue in place during the recording. This design was modified from a chamber described previously (Miller et al, 2001;Cookson et al, 2005). The electrophysiology solution covered half of the leaf area, and the site for impaling was just above the liquid surface.…”
Section: Nitrate-selective Microelectrodesmentioning
confidence: 99%
“…Some recent papers have suggested that there is a close link between cytosolic nitrate activity and nitrate reductase activity (NRA). For example, in leaf cells of Arabidopsis (Cookson et al, 2005) and barley root cells (Fan et al, 2006), changes in cytosolic nitrate activity could be measured under conditions when cellular NRA was altered. As cytosolic nitrate activity is important for determining the thermodynamic gradients for transport to and from the vacuole (Miller and Smith, 1992;De Angeli et al, 2006) how NRA and mRNA expression changed during the remobilization of stored nitrate has also been examined.…”
Section: Introductionmentioning
confidence: 99%